(untitled) (Academia Science Repository, 2023)
Monologue Planning teach students how to plan and structure their monologues effectively. Help them outline their main ideas, supporting details, and logical flow. Emphasize the importance of coherence and organization in monologic speech. Time Constraints, set time limits for monologues to help students learn to express their ideas within a specific timeframe. Gradually increase the time allotted as students become more proficient. This exercise trains students to think quickly, organize their thoughts efficiently, and deliver their monologues concisely.